Pelaporan Indikator Mutu Keperawatan dengan Penerapan Berbasis Teknologi dan Sistem Informasi - Veronica Chain; Rr Tutik Sri Hariyati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to improve the application of unit quality indicator reporting through a digital system that makes it easier for nurses to access so that reports can be submitted quickly and accurately. The method used is a literature review of 11 kinds of literature and various other literature on improving the quality of nursing through the reporting system. The research results show that the basis for nurses in supporting the work program of the Department of Nursing is to maintain the quality of nursing services, which is guided by hospital patient safety. One of them is implementing a technology-based and information system-based nursing quality indicator reporting system. In conclusion, reporting unit quality indicators becomes more accessible, faster, and precise. It becomes an effort to determine the quality of performance and nursing services in each nursing unit, which benefits health workers, hospitals, and the community. Keywords: Nursing Quality Indicators, Hospital Information Systems, Digital Technology